IDNLearn.com: Where your questions meet expert advice and community support. Explore a wide array of topics and find reliable answers from our experienced community members.
Sagot :
Answer:
no solution
Step-by-step explanation:
solve by elemination
Answer:
No solutions
Step-by-step explanation:
4x+2y=−14
4x + 2(-2x - 6) = -14
4x -4x - 12 = -14
0x - 12 = -14
x = 0
y = 2(0) - 6
= 0 - 6
= -6
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Find the answers you need at IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.